Godfatherism, ownership influence and media treatment of political conflicts in Oyo state, Nigeria (2013)
"Media coverage of political crises, especially in a terrain fraught with the increasing influence of godfatherism, ownership and political affiliation has a serious consequence on the society. The political feud between Late Chief Lamidi Ariyibi Adedibu and his „political son‟, Senator Rashidi Adewolu Ladoja in Oyo State, Nigeria (2005-2007), provided a typical example of godfatherism, and media coverage of the conflict typified ownership influence on news media operations. Anchored on the framing theory, this study employed content analysis to examine how The Nigerian Tribune and The Nation newspapers treated the political conflict in terms of the degree of prominence accorded the two principal actors and how ownership factor and political affiliation shaped the contents of the newspapers. Findings show that The Nation, a newspaper believed to be owned by a stalwart of the Action Congress of Nigeria (ACN), was less critical of Senator Rashidi Ladoja and reported more of anti-Adedibu stories. The Nigerian Tribune, on the other hand, reported more of anti-Ladoja stories, and was less critical of Chief Lamidi Adedibu. This paper concludes by urging media actors to free themselves from the web of partisan politics and be more objective in the discharge of their duties as societal watchdogs. "